Phytoseiidae (Acari) in forest fragments in the State of São Paulo, Brazil - Demite, Peterson R. [UNESP]; Lofego, Antonio C. [UNESP]; Feres, Reinaldo J. F. [UNESP] (Magnolia Press, 2011)
Mites of the family Phytoseiidae have been extensively studied as biological control agents of various pests. However, knowledge of these mites in plants of forest fragments in Brazil is still incomplete. The aim of this study was to study the occurrence of Phytoseiidae in forest fragments in the Northwestern of State of São Paulo. Samplings were collected from 18 forest fragments, including 102 plant species belonging to 47 plant families. We recorded 46 phytoseiid species belonging to 17 genera and three subfamilies. Two new species are described, Amblyseius biotafapesp sp. nov. and Amblyseius novagranadensis sp. nov. Trichilia casaretti and Actinostemon communis harbored the largest numbers of species, 29 and 22, respectively. Some species recorded in this study have been frequently reported on cultivated plants. Besides the biological importance of knowing the phytoseiid mite fauna in these forests, survey studies can provide information to support projects on integrated pest management.
Keywords: Conservation; Diversity; Native plants